2018
DOI: 10.1111/ijac.13100
|View full text |Cite
|
Sign up to set email alerts
|

Study on the sintering behavior and characterization of the IGZO ceramics by slip casting

Abstract: High-purity In 2 O 3 , Ga 2 O 3 and ZnO (In:Ga:Zn = 1:1:1) mixtures were employed to fabricate the IGZO (In-Ga-Zn-O) ceramics by slip casting. The rheological properties and zeta potential of IGZO slurry were analyzed in details. The optimum amount of dispersant used in the IGZO slurry is studied in details. This study investigated the relationship between the phase composition of sintered IGZO ceramics and sintering temperatures. The IGZO ceramics with high density and low resistivity are successfully synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Besides, the geometrical density of the pellets was of the order of 80% at this stage. This observation is consistent with recent results that showed that high temperatures are required to obtain dense pellets, of the order of 1300°C‐1400°C, which leads to a difficult compromise between the need for a sufficiently high temperature for the densification, but sufficiently low to limit the volatilization . However, we wish to mention that it has been shown recently that the sintering temperature can be reduced to 1200°C for m = 1 by the assistance of CSP, which may be promising to obtain dense pellets of these homologous compounds if this result can be generalized to the whole series.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Besides, the geometrical density of the pellets was of the order of 80% at this stage. This observation is consistent with recent results that showed that high temperatures are required to obtain dense pellets, of the order of 1300°C‐1400°C, which leads to a difficult compromise between the need for a sufficiently high temperature for the densification, but sufficiently low to limit the volatilization . However, we wish to mention that it has been shown recently that the sintering temperature can be reduced to 1200°C for m = 1 by the assistance of CSP, which may be promising to obtain dense pellets of these homologous compounds if this result can be generalized to the whole series.…”
Section: Resultsmentioning
confidence: 87%
“…This observation is consistent with recent results that showed that high temperatures are required to obtain dense pellets, of the order of 1300°C-1400°C, which leads to a difficult compromise between the need for a sufficiently high temperature for the densification, but sufficiently low to limit the volatilization. 22,24 However, we wish to mention that it has been shown recently that the sintering temperature can be reduced to 1200°C for m = 1 by the assistance…”
Section: Resultsmentioning
confidence: 99%
“…The zeta potentials of In 2 O 3 and Cl-GQDs had different signs, which was helpful for the attachment of Cl-GQDs to In 2 O 3 surface by electrostatic attraction. 41,42 Besides, the zeta potential of Cl-GQDs/In 2 O 3 was 2.6 mV, which proved that the Cl-GQDs were successfully attached to the surface of In 2 O 3 and the simple ultrasonic treatment was feasible. Photoluminescence spectra of In 2 O 3 and Cl-GQDs/In 2 O 3 under excitation of 365 nm were shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…This phenomenon follows the results obtained from phase‐field simulations. CIP enhances the compaction of the powder, reduces the volume of internal pores within the compact, increases the contact points between powder particles, facilitates the channels of material migration, and improves the sintering activity 31,32 …”
Section: Resultsmentioning
confidence: 99%